The Role of International Institutions in the Enforcement of Humanitarian Law in Contemporary Conflicts - Kurnia Hadi; Dilli Setiawan; Tarsisius Susilo; Setiawan Arismunandar; Arinto Beny Sarana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Contemporary wars, such as the Russian invasion of Ukraine since February 2022, the Israel-Hamas conflict in Gaza since October 2023, and the civil war in Yemen since 2014, have caused widespread humanitarian crises: thousands dead, tens of thousands injured, and millions displaced and starving (Janowski, 2025; Al-Mughrabi & Farge, 2025; ACAPS, 2024). In an effort to protect civilians, International Humanitarian Law (IHL) rooted in jus in bello and the 1949 Geneva Conventions along with their Additional Protocols establishes basic protection norms in armed conflicts. This research aims to: (1) identify the roles of the United Nations (UN), the International Committee of the Red Cross (ICRC), and the International Criminal Court (ICC) in the enforcement of IHL; (2) evaluate the actual achievements and structural obstacles faced; and (3) compare the effectiveness of IHL enforcement mechanisms in the three conflicts. The method used is qualitative with a policy study and comparative design. Data were collected from official documents of the UN, ICRC, ICC, NGO reports (Amnesty, HRW), international law journals, and secondary field data from 2021–2025. Thematic analysis and cross-case source triangulation ensure the validity of the findings. The research findings indicate that the UN plays a role in normative advocacy and humanitarian assistance but is hindered by the Security Council's veto power; the ICRC carries out the mandate to protect victims but relies on access and negotiation with conflicting parties; while the ICC is only effective if the conflict countries ratify the Rome Statute, as in the case of Ukraine, whereas its jurisdiction over Israel and Yemen is limited. This study concludes that although international institutions strengthen HHI norms, political and legal constraints demand reform of the veto mechanism, expansion of ICC jurisdiction, and guarantees of unhindered humanitarian access. Keywords: Contemporary Conflicts, International Humanitarian Law, International Institutions, Protection of Civilians, War Law Enforcement.